2015
DOI: 10.1136/jfprhc-2014-101153
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective evaluation of the intrauterine device in a patient population in Buenos Aires, Argentina

Abstract: Findings suggest overall good long-term performance with IUD insertion, with minimal complaints or adverse outcomes. These findings may help to support providers serving similar populations in promoting this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The rapid expansion of PPCuIUD — in India as well as globally — calls for more evidence on the outcomes of these programs in terms of continuation rates at 1 year and beyond. While global evidence on continuation rates is available for interval intrauterine contraceptive device (IUCD) insertions [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , it is limited for PPCuIUDs. The few studies on PPCuIUD continuation rates are restricted to hospital settings [18] , [19] , [20] , but there is little evidence from any program implemented at scale [21] .…”
Section: Introductionmentioning
confidence: 99%
“…The rapid expansion of PPCuIUD — in India as well as globally — calls for more evidence on the outcomes of these programs in terms of continuation rates at 1 year and beyond. While global evidence on continuation rates is available for interval intrauterine contraceptive device (IUCD) insertions [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , it is limited for PPCuIUDs. The few studies on PPCuIUD continuation rates are restricted to hospital settings [18] , [19] , [20] , but there is little evidence from any program implemented at scale [21] .…”
Section: Introductionmentioning
confidence: 99%
“…Rates of discontinuation due to bleeding were reported in eight studies [ 33 , 35 39 , 41 , 42 ]. Rates were < 5% in a large 5-year retrospective study [ 36 ], a cross-sectional study performed in Brazil [ 37 ] and for the smaller Cu-IUDs, VeraCept175 and Mini TT380 Slimline [ 41 , 42 ], whereas in other studies (including for the comparator group in the studies of VerCept175 and MiniTT380) the reported rates for individual studies ranged from 8.5 to 22%. Thus, in most studies, bleeding (and pain) was the reason for discontinuation in over a third of women choosing to have Cu-IUDs removed.…”
Section: Resultsmentioning
confidence: 99%